Ultracapacitor applications - Miller, John M., 1949- (London : Institution of Engineering and Technology, 2011)
This text takes a critical look at physical storage of electricity in the devices known collectively as electrochemical capacitors and particularly as ultracapacitors.
1. Types of ultracapacitors -- 2. Ultracapacitor modeling -- 3. Power and energy -- 4. Commercial applications -- 5. Industrial application -- 6. Heavy transportation application -- 7. Hybrid electric vehicles -- 8. Single-mode power split -- 9. 2-mode power split -- 10. Life cycle testing -- 11. Abuse tolerance -- 12. Future transportation systems.
Includes bibliographical references and index.
Keywords: Supercapacitors